Managing Exercise-Induced Bronchoconstriction: A Comprehensive Review of Strategies for Athletes to Maintain Fitness and Health - Genta Dwi Putra; Arsil Arsil; Tjung Hauw Sin; Ardo Okilanda; Dally Rahman; Yovhandra Ockta (Jurnal Penelitian Pendidikan IPA, 2024)
Exercise-induced bronchoconstriction (EIB) significantly impacts athletes by impairing their performance and overall health. Characterized by airway narrowing during or after physical activity, EIB affects the quality of training and competition. This study employs a qualitative descriptive research model based on a comprehensive literature review to evaluate EIB management strategies in athletes. We systematically collected data from trusted scientific databases—Scopus, Science Direct, and Google Scholar—using keywords such as "Exercise-Induced Asthma," "Athlete," and "Sport." Relevant articles were identified, and key terms related to EIB management were reviewed. The data, including study designs, research objectives, sample sizes, and findings, were compiled and analyzed to determine effective management approaches. Key findings indicate that accurate diagnosis using spirometry and bronchial provocation tests is essential. Pharmacological management primarily involves inhaled corticosteroids (ICS) to reduce inflammation and control EIB, while short-acting beta agonists (SABAs) offer only temporary relief. Non-pharmacological strategies include avoiding triggers, implementing proper warm-up routines, and using breathing techniques. Supervised aerobic exercise programs were shown to improve cardiovascular fitness without worsening EIB symptoms. The study also reviewed the impact of environmental factors, such as air pollution and post-COVID-19 conditions, on EIB. Recommendations include personalized asthma action plans, training for coaches on environmental triggers, and exercising in controlled conditions. This study highlights the need for a holistic approach combining pharmacological and non-pharmacological methods to manage EIB effectively and maintain athletic performance. Further research is warranted to develop tailored strategies for athletes with EIB.